Environmental science : protect our planet - Mosteiro, Arnaldo P. (Manila, Philippines : Educational Publishing House, 2012)
This book entitled, environmental science, has been prepared in response to the need for environmental education for undergraduate and graduate studies in colleges and universities and for the general public.
Introduction -- Ecological principles and concepts -- Seven environmental principles -- Ebergy flow through ecosystem -- Biogeochemical cycles -- Biomes -- Air pollution -- Water pollution -- Land pollution -- Human population -- Biodiversity -- Energy and environment -- Global forest and environment -- Industrialization and urbanization -- Global environmental issues and concerns -- A Stategy and actions for sustianable living and development
Includes bibliographical references.
Keywords: ENVIRONEMTAL SCIENCES -- TEXTBOOK